Brazilian art under dictatorship : Antonio Manuel, Artur Barrio, and Cildo Meireles - Calirman, Claudia (Duke University Press, 2012)
After the Brazilian military took power in a coup in 1964, many artists tried to distance themselves from politics; others went into exile. This book covers the most culturally repressive years of the regime, from 1968-74 and looks at artists who found their own visual language of resistance, outside government-controlled cultural centers or the militant left.